Pengaruh Kekuatan Otot Lengan, Kekuatan Otot Tungkai Dan Kelentukan Togok Terhadap Kecepatan Renang 50 Meter Gaya Dada - Syaiful, Andi; Wainggai, Heppy Hein; Muhaemin, Ince Abdul (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This descriptive study employed a path analysis design to examine the influence of arm muscle strength, leg explosive power, and trunk flexibility on breaststroke swimming ability. The study population consisted of students from the Physical Education Department at FKIP Uncen, with a sample of 30 students from the 2022 cohort selected using simple random sampling. Data analysis included descriptive statistics, assumption testing, and path analysis using SPSS version 25.00 with a significance level of 5% (α = 0.05). The results showed that: (1) arm muscle strength had a direct effect on flexibility (ß = 0.679; p = 0.016); (2) leg explosive power had a direct effect on flexibility (ß = 0.964; p = 0.028); (3) arm muscle strength had a direct effect on breaststroke swimming ability (ß = 0.555; p = 0.001); (4) leg explosive power had a direct effect on swimming ability (ß = 0.756; p = 0.029); (5) flexibility had a direct effect on swimming ability (ß = 0.854; p = 0.016); (6) arm muscle strength had an indirect effect on swimming ability through flexibility (ß = 0.579; p = 0.000256); and (7) leg explosive power had an indirect effect on swimming ability through flexibility (ß = 0.823; p = 0.000448). Overall, this study demonstrates that arm muscle strength, leg explosive power, and trunk flexibility significantly influence breaststroke swimming performance both directly and indirectly among students of the Physical Education Department at FKIP Uncen.